Atomically dispersed manganese sites embedded within nitrogen-doped carbon nanotubes for high-efficiency electromagnetic wave absorption. (15th October 2022) - Wang, Yuping; Shi, Yanan; Zhang, Xiao; Yan, Feng; Zhang, Jianzhong; Zhang, Xitian; Chen, Yujin; Zhu, Chunling
Abstract: It is highly desirable for electromagnetic wave (EMW) absorbers to have a low high filler ratio in matrix and low matching thickness. Herein, atomically dispersed Mn sites are introduced into N-doped carbon nanotubes (Mn−Nx /NCNT) to this aim. Structural characterizations indicate that the as-fabricated Mn−Nx /NCNT exhibits tubular morphology with a large surface area of 295.56 m 2  g −1 and the Mn sites are atomically dispersed in the NCNT with a loading of 1.56 wt%. Benefiting from the unique structural advantages, Mn−Nx /NCNT has excellent EMW absorption property, showing an effective absorption bandwidth of 4.15 GHz at a filler ratio of only 7% and a matching thickness of only 1.7 mm. The experimental measurements of electromagnetic parameters and density functional theory calculation results indicate that electronic structure and polarizability of the NCNTs are adjusted by the atomically dispersed Mn sites, leading to the increase in conduction and polarization losses of Mn−Nx /NCNT, and thus in the EMW property. Our results demonstrate that hollow nanotubes containing metal single-atoms are potential EMW absorbers with a lightweight feature. Graphical abstract: Image 1